(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In the article, first, general information about the literature analysis of macroeconomic stability is given. then, the history of ensuring macroeconomic stability is highlighted. as well as the main aspects of ensuring macroeconomic stability and the main factors and conditions of ensuring macroeconomic stability, the main attention is paid to effective solutions.